Survivability of Malaysian mosques during the COVID-19 pandemic: a systematic review / Nazmi Qayyum, Mohd Nizam Sahad and Wan Hishamudin Wan Jusoh - Qayyum, Nazmi; Sahad, Mohd Nizam; Wan Jusoh, Wan Hishamudin (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2023)
The COVID-19 pandemic has affected numerous institutions and facilities in Malaysia, impacting religious events and mosques. The COVID-19 pandemic has prompted the Malaysian government to issue a Movement Control Order (MCO) and standard operating procedure (SOP) for congregational prayer during the pandemic as a safety measure to curb the spread of the pandemic. However, this decision affects the mosque’s economy. Due to the lack of systematic review on the survivability of Malaysian mosques during the COVID-19 pandemic, this paper will undertake this topic. Several databases were used to amass research papers using the PRISMA method. Finally, 16 research papers were collected. Four themes were then drawn from all the research, with mosque management ranking the best, followed by worship’s standard operating procedure (SOP), communities’ role, and digital application. The results reveal numerous studies on mosque management to adapt with SOP, but a lack of guidelines in ensuring the sustainability of mosque finance during the pandemic. This study alerts the authorities to solve this issue so they will be more prepared if MCO happens again.